Impact of early heparin therapy on outcomes in patients with solid malignancy associated sepsis: a marginal structural model causal analyse - Huang, Jia-jia; Cai, Ji-zhen; Zhou, Zhi-peng; Liu, Yan; Yang, Zhen-jia; Li, Da-zheng; Chen, Yu-hua; Luan, Ying-yi; Yao, Yong-ming; Wu, Ming (Frontiers in Pharmacology, 2023)
Background Previous studies documented that heparin can inhibit the invasion and metastasis of tumors, but its role on outcomes in patients with solid malignancy complicated sepsis remains unclear.Methods: A retrospective cohort study was conducted in critically ill patients with solid malignancy associated sepsis from the Medical Information Mart for Intensive Care (MIMIC)-IV database. The primary endpoint was intensive care unit (ICU) mortality, secondary outcomes were thrombosis and hospital mortality. Propensity score matching (PSM), marginal structural Cox model (MSCM), cox proportional hazards model,stratification analysis and E-value were used to account for baseline differences, time-varying confounding and unmeasured variables.Results: A total of 1512 patients with solid malignancy complicated sepsis were enrolled, of which 683 in the heparin group with ICU mortality, thrombosis rate and hospital mortality were 9.7%, 5.4%, 16.1%, and 829 in the non-heparin group with ICU mortality,thrombosis rate and hospital mortality were 14.6%, 12.5%, 22.6%. Similar results were observed on outcomes for patients with PSM (ICU mortality hazard ratio [HR] 0.61, 95% confidence interval [CI] 0.41-0.92), thrombosis rate (HR 0.42, 95% CI 0.26-0.68); hospital mortality HR 0.70, 95% CI 0.50-0.99). MSCM further reinforced the efficacy of heparin in reducing ICU mortality (HR 0.48, 95% CI 0.34-0.68). Logistic regression and Cox regression model showed heparin use also markedly reduced thrombosis (HR 0.42; 95% CI 0.26-0.68; P<0.001) and hospital mortality (HR 0.70; 95% CI 0.50-0.99; P=0.043). Stratification analysis with the MSCM showed an effect only those with digestive system cancer (HR 0.33, 95% CI 0.16-0.69).Early heparin therapy improved outcomes in critically ill patients with solid malignancy complicated sepsis. These results are evident especially in those with digestive system cancer. A prospective randomized controlled study should be designed to further assess the relevant findings.